Exploring the Role of Parent–Child Emotional Bonding and Verbal Interaction in Early Speaking Development - Saefudin, Dery Purnama; Wulandari, Wenny; Wahjuningtijas, Rindang (SALEE: Study of Applied Linguistics and English Education, 2025)
Early language development is crucial for children’s cognitive and social growth. This study aims to investigate the relationship between parental linguistic stimulation, emotional support, and children’s speaking ability. The research involved 30 preschool and kindergarten children at KB-TK Amanah Qurani in the 2024/2025 academic year. Data were collected using questionnaires completed by teachers and parents. Due to non-normal distribution in two variables, Spearman Rank Correlation was used for analysis. Results show significant positive correlations among all variables. Parental linguistic stimulation and emotional support are strongly correlated (? = 0.735, p < 0.001). Children’s speaking ability has a moderate positive correlation with linguistic stimulation (? = 0.573, p = 0.001) and a strong positive correlation with emotional support (? = 0.640, p < 0.001). These findings indicate that higher parental involvement in language and emotional development is associated with better speaking skills in early childhood. This study emphasizes the vital role of both cognitive and emotional support in language acquisition and recommends greater focus on parent-child interaction in early education programs.